1 answer:
Answer:
Step-by-step explanation:
(2x + 3) (-x - 2)
distribute first term, to the second term:
2x(-x) + 2x(-2) + 3(-x) + 3(-2)
multiply:
+ (-4x) + (-3x) + (-6)
combine the like terms:
- 4x - 3x - 6
-7x
- 7x - 6
final answer :
- 7x - 6
hope this helped !!
mark me brainliest :D
You might be interested in
Answer:
25.333332 years
Step-by-step explanation:
19/3
=6.333333*4
Answer:
b
Step-by-step explanation:
100 plus 400 doesn't equal 900
15x^2-11xy-3y^2
Thats the answer
Answer:
x=9
Step-by-step explanation:
x/3+5=8
x/3=8-5
x/3=3
(x/3)*3=3*3
x=9
double check
9/3+5=8
3+5=8
8=8